2008
DOI: 10.1371/journal.pbio.0060120
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic Individuality in the Host–Phage Interaction

Abstract: Isogenic bacteria can exhibit a range of phenotypes, even in homogeneous environmental conditions. Such nongenetic individuality has been observed in a wide range of biological processes, including differentiation and stress response. A striking example is the heterogeneous response of bacteria to antibiotics, whereby a small fraction of drug-sensitive bacteria can persist under extensive antibiotic treatments. We have previously shown that persistent bacteria enter a phenotypic state, identified by slow growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 32 publications
7
99
0
3
Order By: Relevance
“…While normal cells are believed to resume growth and become susceptible to antibiotics immediately after transfer into fresh medium, persisters remain dormant longer (28). Here we demonstrate that heterogeneous growth resumption is an intrinsic property of the whole E. coli population.…”
mentioning
confidence: 58%
“…While normal cells are believed to resume growth and become susceptible to antibiotics immediately after transfer into fresh medium, persisters remain dormant longer (28). Here we demonstrate that heterogeneous growth resumption is an intrinsic property of the whole E. coli population.…”
mentioning
confidence: 58%
“…Having found that HipA-arrested cells are fully metabolically active, we next sought to exploit the active carbon flux within HipAarrested cells to produce useful compounds via synthetic pathways. One advantage of using growth-arrested bacteria as a platform for the production of chemicals might be their higher resistance to phage-induced lysis compared with that of growing cells (38). Industrial-scale fermentations are extremely vulnerable to contamination by phage, which often causes considerable production losses.…”
Section: Resultsmentioning
confidence: 99%
“…The capability of T cells to access multiple programs for cytokine release allows diverse and dynamically evolvable contributions to the sustained accumulation of cytokines in the global milieu, and such behavior represents an intriguing manifestation of modularity, cell-to-cell communication, and feedback. The adaptability of multicellular systems to temporal and environmental fluctuations is yet another quality that improves when the collective population comprises phenotypically diverse individuals (34)(35)(36). Dynamically evolving functional responses by T cells, therefore, suggest an alternate form of functional plasticity (37) and may provide yet another means for the immune system to adaptively respond to perturbations.…”
Section: Discussionmentioning
confidence: 99%